The next era of electrification: engineering adaptive energy infrastructures for a decarbonized society - Tole Sutikno (Institute of Advanced Engineering and Science, 2026)
A new era of electrification is reshaping electrical engineering, with adaptive energy infrastructures becoming critical foundations for achieving resilient, low-carbon, and sustainable energy systems. Rapid advances in renewable energy integration, power electronics, distributed energy resources, battery energy storage, electrified transportation, and intelligent energy management are transforming conventional power systems into flexible, interconnected, and resilient infrastructures. This editorial discusses the emerging paradigm of adaptive electrification, in which future electrical networks are expected to dynamically coordinate generation, energy storage, conversion, transmission, distribution, and consumption across increasingly decentralized environments. Beyond traditional objectives of efficiency and reliability, next-generation electrical infrastructures must address growing electricity demand, carbon neutrality, power quality, climate resilience, cyber-physical security, and energy accessibility. The editorial further highlights several promising research directions, including grid-forming power electronics, adaptive microgrids, intelligent battery management, solid-state energy conversion, digitalized power infrastructures, resilient hybrid AC/DC systems, and coordinated human–AI decision-making. Collectively, these technological advances position electrical engineering at the forefront of the global energy transition, emphasizing that future electrification requires not only cleaner energy sources but also adaptive, intelligent, and sustainable infrastructures capable of continuously evolving to meet societal, environmental, and industrial challenges while supporting reliable and equitable access to electricity.